Zoning of the Southern Buh River Basin Under the Conditions of Spring Flood Formation - Dokus, A. O.; Shakirzanova , ZH. R. (Man and Environment. Issues of Neoecology, 2021)
The Southern Buh river basin is located in three natural zones of Ukraine and is heterogeneous in terms of physical and geographical conditions of river runoff formation. Purpose. Carry out hydrological zoning of the Southern Buh river basin with the allocation of areas with the same conditions for the spring floods formation by a set of morphometric characteristics of rivers and their basins and hydrometeorological and agrometeorological factors. Methods. Using a statistical model of factor analysis (R-modification) the most significant factors from the totality of all features were identified. There are two factors – the first describes 38% of the total variance of all factors (latitude of catchment centers, average height of catchments, wetlands, water reserves in the snow cover, precipitation of snowmelt and maximum depth of soil freezing), and the second – 21% (river length, catchment area and the amount of precipitation that fell after snowmelt). Factor loads were used for further grouping of basins using the method of cluster analysis. Results. As a result of territory zoning, two hydrological districts with sub-districts (district I and district II with sub-districts IIa, IIb, IIc) were identified. Area I covers the area from the source to hydrological post on the Southern Buh river basin – Trostyanchik village. Downstream and to the river mouth, the territory covers area II, which is divided into three sub-areas (sub-area IIa, IIb, IIc). Data from small rivers between the Dniester and the Southern Buh are involved in the hydrographical network. The boundaries of hydrological districts in the Southern Buh river basin were drawn along the watersheds of rivers, taking into account the physical and geographical zoning of the territory and involving in the analysis of maps of soil cover and vegetation in the basin. The hydrological zoning of the Southern Buh river basin under the conditions of spring flood formation is in good agreement with the zoning of the plain territory of Ukraine, which was performed by different authors over time. Conclusions. The use of statistical methods in the work allowed to clarify the boundaries of existing districts and identify new sub-districts in the Southern Buh river basin. The analyzed natural conditions have shown that within the limits of hydrological zoning they have certain features of spring floods formation. Such features will be used in the substantiation of the regional method of long-term forecasting of the characteristics of spring flood in the Southern Buh river basin.